Sensitivity Analysis of Helical Gears with Tooth Surface Modification to Applied Torque and Gear Misalignment (Xibei Gongye Daxue Xuebao, 2018)
The numerical calculation model of time-varying mesh stiffness, static transmission error and composite mesh error of modified helical gears is developed based on loaded tooth contact analysis (LTCA) model. To minimize the fluctuation of vibration excitation force, the optimal modification parameters of three modification methods under designed applied torque and ideal tooth contact condition are determined, and the effects of three modification methods on time-varying mesh stiffness, static transmission error and composite mesh error are analyzed. In order to analyze the sensitivity of the three modification methods to applied torque and gear misalignment, the effects of applied torque in wide range and gear misalignment on vibration excitation force and dynamic transmission error are investigated. The results show that the difference of time-varying mesh stiffness, static transmission error, composite mesh error of helical gears with different modifications methods are obvious. However, the fluctuation of vibration excitation force of helical gears is reduced significantly. When the applied torque is higher than the designed applied torque, the three modification methods show a great reduction of system vibration. When the applied torque is too low, the vibration of modified helical gears is larger than unmodified ones. Meanwhile, the resonance speed of the helical gears is slightly lower. With the increase of gear misalignment, the resonance speed becomes lower correspondingly and the effect of the three modification methods on the reduction of vibration excitation force is not obvious any more. The results can provide effective reference for establishing robust optimization method for tooth surface modification.